TAJAM KEBAWAH, TUMPUL KEATAS? WUJUD KEADILAN HUKUM DI INDONESIA - Kenny Prawiro; Chris Anggi Natalia Berutu (Honeste Vivere, 2026)
This study examines the inequality in law enforcement in Indonesia, often described as “sharp downward, blunt upward,” which reflects the injustice in implementing the principles of justice, expediency, and legal certainty. The purpose of this research is to illustrate how justice, expediency, and legal certainty are realized in the current practice of law in Indonesia, and to explain how to establish the relationship between das sein (legal reality) and das sollen (the ideal purpose of law). The method used is descriptive juridical research, with analysis of primary and secondary legal materials (legislation, court decisions, and case studies) to map the gap between legal reality and legal ideals. The results show that although legal norms and formal principles are well established, the implementation of substantive justice and expediency is often disrupted by sentencing disparities, political interference, and unequal access to justice. In conclusion, achieving true legal justice requires harmonization between ideal legal norms, public morality, and transparent governance so that the law applies not only to certain groups but to all levels of society.